Geotechnical Characteristic Assessments of Floodplain Soils Using SCPTU Data in Nanjing, China. (22nd April 2022) - Zhang, Mingfei; Tong, Liyuan; Wang, Qiang
Abstract : In order to improve the understanding of such floodplain sediments and determining the validity of the tests, an extensive series of multifunctional seismic piezocone tests with pore pressure dissipation phase have been performed and supplemented with conventional borings, standard penetration, laboratory testing, and so forth. Sounding results from SCPTU were used to determine the stratigraphic profiles and the soil characteristics of two anchorage sites. A comparison of the boring and laboratory results with the CPTU profiles showed that the CPTU provided excellent information on soil stratigraphy and good guidance for determination of behavior and engineering implications of recent Yangtze River floodplain. At an area where local correlations based on modern SCPTU do not exist, methods for estimating coefficient of earth pressure at rest ( K 0 ), hydraulic permeability ( k h ), and equivalent stiffness ( G 0 ) associated with bridge foundation design are presented, compared, and verified. Results also illustrate the complexity and variability of the floodplain stratigraphy and soil properties, which means that the suggestions in this study should be updated when more local experience is obtained. This case study suggests that such enhanced seismic piezocone test should be considered as a potential tool and the instrument of first choice in site characterization programs for design of bridges founded on complicated soils in China.